The design and control of a 3DOF lower limb rehabilitation robot. (February 2016) - Wu, Junpeng; Gao, Jinwu; Song, Rong; Li, Rihui; Li, Yaning; Jiang, Lelun
Abstract: Aiming to assist stroke patients who suffer from motor dysfunction after stroke and reduce the stress of physiotherapists, a 3-degree-of-freedom (3DOF) lower limb rehabilitation robot (LLRR) has been developed for the motion recovery in this paper. At first, a simple and flexible structure of LLRR is designed, which involves hip, knee and ankle joints and can also be adjusted to fit for the different heights of patients. Then, for the controller design, control-oriented model of LLRR is studied and validated by both simulation and experiments, including the kinematic model of mechanical system, friction model of rotation joints and motor model of actuators. Based on the proposed models, an adaptive robust sub-controller is synthesized to make each joint track its designed training trajectory, overcome system uncertainties and reject the disturbances from patient. At last, experiments are carried out to validate the proposed LLRR by the passive movement training.